Expression of activating receptors on natural killer cells from AIDS-related lymphoma patients - Mercier-Bataille, Delphine (AIDS Res Ther, 2014)
BACKGROUND: Abnormal NK phenotype and cytotoxic functions have been described in acute myeloid leukemia, chronic lymphocytic leukemia, myeloma and myelodysplastic syndromes. Defective NK cytotoxicity is due to decreased expression of the Natural Cytotoxicity Receptors (NCRs), 2B4/CD244/p38, or NKG2D. This prompted us to test the expression of these molecules on circulating NK cells from patients with AIDS-related lymphomas (RL) in comparison with HIV + patients without lymphoma, healthy subjects and HIV-negative patients with lymphoma. METHODS: Blood samples were analyzed by flow cytometry for NCRs, 2B4/CD244/p38 and NKG2D expression on NK cells defined as CD3-/CD56+ lymphocytes. We also analyzed by quantitative PCR specific RNA for NKp30/NCR3 and NKp46/NCR1. RESULTS: We could not detect any defect in NKp46/NCR1 expression between all groups. NKp44/NCR2, NKp30/NCR3 and NKG2D had lower expression in AIDS-RL in comparison with HIV + patients without lymphoma when compared to patients with similar (>0.3 G/L) CD4+ lymphocyte levels. Expression of 2B4/CD244/p38 was lower in AIDS-RL than in HIV-negative lymphoma. Comparison of specific NKp30/NCR3 and NKp46/NCR1 RNA showed increased steady state levels, despite decreased surface expression for NKp30/NCR3, suggesting abnormal post-transcriptional regulatory mechanisms. CONCLUSIONS: We show a more pronounced defect in NK activating molecule when HIV infection is associated with lymphoma than when only one condition (HIV positivity or lymphoma) is present. Defective NK phenotype, in addition to CD4+ depletion and dysfunction, may participate to the increased incidence of lymphoma in HIV patients.